AS A SPORTS SOCIALIZATION AGENT - Akramov Hassan Furkatovich; Abdurazakova Kamolakhan Yusupovna (Scholar Express Journal, 2023)
This article reveals the process of socialization from a scientific-theoretical point of view, and talks about the conditions of socialization in the field of sports, which is a socio-cultural process. It has been shown that the educational functions of sports are realized with this social flow. The sports field of socialization, which is considered an important social relationship in the implementation of interpersonal communication, is cited as an agent. In it, the role of sport as a socio-ethical and socio-cultural mechanism is fully and scientifically described
Keywords: socialization; sport; scientific-theoretical analysis; agent